Treatment results and prognostic factors of clear cell ovarian carcinomas and ovarian carcinomas with clear cell component - M. D. Ahmedova; M. A. Shabanov; V. V. Barinov; K. I. Zhordania; L. I. Bokina; E. A. Mustafina; I. I. Bokin; D. B. Olkin (Опухоли женской репродуктивной системы)
The most important prognostic factors for clear cell carcinoma (CCC) are clinical and morphological signs and clinical stage of the disease. Analyses of 5-year survival in patients with I stage of CCC is 69 %, in II stage – 55 %, in III stage – 14 % and in IV stage – 4 % patients. We analyzed distant results of treatment of 71 patients with CCC and of 25 patients with mixed malignant ovaries neoplasm with obligatory clear cell component taking into consideration main clinical and morphological sings of disease. On the base of performed reseal we revealed that morphological structure of the tumors and stage of the disease exerted heist influence on the exponent of survival of the patients with clear CCC ovaries neoplasm. Besides, there is a correlation between exponent of patients’ survival and radicalized of surgery, character of tumor growth, differentiation degree, cell anaplasia and mitotic activity of tumor cells.